Exchange Market Pressure and Monetary Policy: The Turkish Case - Siklar, Ilyas; Akca, Aysegul (Ekonomika, 2020)
The purpose of this study is to determine the relationship between monetary policy and the exchange market pressure index in Turkey for the 2002–2018 period with monthly data. To obtain the foreign exchange market pressure index, this study uses the model developed by L. Girton and D.E. Roper and is based fundamentally on the monetary approach to exchange rate determination and the balance of payments. The calculated exchange market pressure index is in accordance with the developments lived in financial markets and changes in monetary policy during the period under investigation. As for the relation between exchange market pressure index and monetary policy, a VAR model was set up and a Granger type causality analysis was carried out. According to Granger causality test results, there is a unidirectional causality running from domestic credit expansion to exchange market pressure and from domestic credit expansion to interest rate differential while there is a bidirectional causality between exchange market pressure and interest rate differential. Since increasing exchange market pressure means a depreciation of the Turkish Lira, the estimated VAR model’s results support the view that the Central Bank will increase the interest rate to temper the exchange market pressure.
Keywords: Exchange market pressure index; Monetary policy; Girton-Roper Model